2008
DOI: 10.1007/s10552-008-9227-5
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic polymorphisms of AURKA and prostate cancer risk

Abstract: The two investigated SNPs in AURKA were not found to be associated with prostate cancer risk. Other common SNPs of AURKA should be investigated in further studies because of its location on a prostate cancer susceptibility locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Although the Phe/Phe polymorphism is common and the Phe/Ile variant is more frequently found in tumour tissues, no correlation of either variant with the course or outcome of the disease could be found. Nevertheless, the AurkA polymorphism has been observed in many tumour types, e.g., oesophageal, breast, hepatocellular, and prostate cancer [17, 35-38]. Miao et al found a 44.2% frequency of the heterozygous allele in oesophageal tumour patients, the same range as found in the present study (49%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the Phe/Phe polymorphism is common and the Phe/Ile variant is more frequently found in tumour tissues, no correlation of either variant with the course or outcome of the disease could be found. Nevertheless, the AurkA polymorphism has been observed in many tumour types, e.g., oesophageal, breast, hepatocellular, and prostate cancer [17, 35-38]. Miao et al found a 44.2% frequency of the heterozygous allele in oesophageal tumour patients, the same range as found in the present study (49%).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, the frequency of the Ile/Ile polymorphism found in other tissues was clearly higher at 47.0% [17]. The prognostic value of either polymorphism, however, is unclear and remains controversial [17, 35-38]. …”
Section: Discussionmentioning
confidence: 99%
“…The Taqman allelic discrimination method (Applied Biosystems, Darmstadt, Germany) was used to genotype rs8173 and rs2273535 [25]. For rs8173, the assay information was kindly provided by Dr. A. Gsur [26]. Detection was performed using an ABI PRISM 7900HT Sequence Detection system with SDS2.2 software (Applied Biosystems).…”
Section: Genotypingmentioning
confidence: 99%
“…This analysis showed that the I31 allele increases the risk ofmultiple cancer types and confirmed the I31 allele is a low‐penetrance cancer susceptibility allele. Nonetheless, it should be noted that some studies, including breast cancer, prostate cancer, gastric cancer and mantle cell lymphoma, have found no association with Aurora A I31 allele [24–26,29,30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control studies have investigated the association between F31I polymorphism of Aurora A gene and cancer risk [21][22][23][24][25][26][27][28][29][30][31][32]. However, the results have not been consistent, although a meta-analysis of 15 case-control studies concerning Aurora A F31I polymorphism showed that carriers of the I31 allele had an increased risk of multiple cancers [20].…”
Section: Introductionmentioning
confidence: 99%